A Case of macro-TSH masquerading as subclinical hypothyroidism. Issue 7 (12th July 2021) - D'Arcy, Robert; Hunter, Steven; Spence, Kirsty; McDonnell, Margaret
Abstract : A 47-year-old man was commenced on levothyroxine following a diagnosis of subclinical hypothyroidism with nonspecific symptoms. Despite increasing doses of levothyroxine, his thyroid-stimulating hormone (TSH) remained elevated and he was referred for further assessment as he was unable to tolerate further titration. On assessment, his thyroid function demonstrated an elevated TSH and elevated free-T4. The initial impression was of iatrogenic thyrotoxicosis, with possible underlying thyroid hormone resistance, TSHoma or assay interference. After discontinuation of levothyroxine, free-T4 normalised but TSH remained elevated. There was a normal response to thyrotropin-releasing hormone (TRH) testing. T3 suppression testing demonstrated free-T4 reduction but persistently high TSH. THRβ sequencing was normal. TSH measurement by alternative assays revealed discrepant results. Gel filtration chromatography revealed the presence of high-molecular weight TSH variant alongside normal TSH. Macro-TSH is a rare phenomenon with spuriously elevated TSH and which may mimic subclinical hypothyroidism. Recognition of macro-TSH avoids misdiagnosis and prevents inappropriate treatment.